Clinical and epidemiological comparison of patients affected by palmoplantar plaque psoriasis and palmoplantar pustulosis: a case series study. (5th June 2013) - Brunasso, A.M.G.; Puntoni, M.; Aberer, W.; Delfino, C.; Fancelli, L.; Massone, C.
Abstract : Summary Background In 2007 the International Psoriasis Council proposed that palmoplantar pustulosis (PPP) should be considered a separate condition from psoriasis, despite the presence of certain phenotypes common in both diseases. Objectives To describe and compare demographic and clinical characteristics among patients with PPP and palmoplantar plaque psoriasis. Methods This was a retrospective case series study from 2005 to 2010. The following data were obtained: age, sex, family history, smoking habits, nail involvement, joint involvement, disease duration, lesion morphology (plaque or pustular), histological diagnosis, comorbidities, and Physician's Global Assessment (PGA) score for extrapalmoplantar lesions. The sample size calculation indicated that 80 patients, 40 patients for each group (palmoplantar plaque psoriasis and PPP) were needed to see clinically relevant differences between groups. Results Ninety patients were selected, 51 with palmoplantar plaque psoriasis and 39 with PPP. No statistically significant differences were registered between patients affected by PPP and palmoplantar plaque psoriasis as regards age at onset of the disease (48 vs. 44 years; P = 0·4), disease duration (6 vs. 10 years; P = 0·1), family history of psoriasis (28% vs. 33%; P = 0·7), concomitant arthritis (26% vs. 25%; P = 1·0), or smoking habits (54% vs. 41%; P = 0·2). We observed a female predominance ( P = 0·01) and a lesser frequency of nail involvement ( P = 0·03) in patients affected by PPP. Conclusions Our data suggest a close relationship between PPP and psoriasis. The existing data concerning epidemiology, clinical presentation, genetics, histopathology and pathogenesis do not permit a clear distinction between these two entities, which seem to coincide in many aspects. PPP appears to have a marked predilection among female smokers. Abstract : What's already known about this topic? Recently, palmoplantar pustulosis (PPP) has been proposed as a separate condition from psoriasis. What does this study add? We were not able to find significant differences between patients with PPP and those with palmoplantar plaque psoriasis regarding psoriasis, anamnesis, comorbidities or associated extrapalmoplantar psoriasis lesions. Our data suggest a close relationship between PPP and psoriasis. Available data concerning epidemiology, genetics, histopathology and pathogenesis do not permit a clear distinction between psoriasis and PPP.